National strategy to develop the reality of statistical work in meeting the needs of sustainable development in the Syrian Arab Republic - زكريا الزلق; رانيا حسن (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Statistics system a country has forms the main artery that gives life to all it Institutions. Then the statistic is the subject that decision makers relay on in all fields like development, social, economic and demographical. Therefore, for that the need to launch a Statistical strategic project is necessary, works on finding solution moving our country from an acceptable to excellent situations that meets the need of continuous development and forms a pillar for sustainable development in Syria. The present research suggests Statistical methodology relayed on studying a number of Arabian, regional and national forms with the intention to understand them and adopt how it work. That makes the foundation to achieve based on analyzing the current situation and observing number of experiments that enrich the research in a Methodological way and shows how to move to a Statistical system High degree of efficiency in achieving the requirements of sustainable development.